Developing Grade 3 Student Science Learning Achievement and Scientific Creativity Using the 6E Model in STEAM Education - Pattama Jongluecha,; Wittaya Worapun, (Journal of Educational Issues, 2024)
The purposes of the studies were 1) to study the effects of the 6E learning model on grade 3 students’ learning achievement in science with the determining criteria of 70; 2) to compare students’ scientific creativity before and after implementing the 6E learning model; and 3) to evaluate grade 3 students’ creative abilities after implementing the 6E learning model. The participants were 19 students in a public school in Thailand. They were selected by a purposive random sampling. The instruments were a learning management plan designed using the 6E learning model, a learning achievement test, a pre-post-test for creativity assessment, and a creative ability evaluation form. The data were analyzed using the percentage, mean score, standard deviation, median, and Wilcoxon signed-rank test (Z score). The results of the study show that the 6E learning model was effective in transferring the knowledge of science to the grade 3 students. It was also beneficial in developing participants’ creative thinking and ability. The study contributes to the area of STEAM education as it provides evidence to support its effects on a younger group of learners.